Analysis of graphic calculator strategy using cognitive load theory - Mohd Tajudin, Nor'ain; Ahmad Tarmizi, Rohani; Wan Ali, Wan Zah; Konting, Mohd Majid (Malaysian Educational Technology Association, 2007)
Based on cognitive load theory, two phases of quasi-experimental nonequivalent control-group posttest only design studies were conducted to investigate the effects of using graphic calculator strategy in mathematics teaching and learning on Form Four Malaysian secondary school students’ performance. The possibility that the use of graphic calculators can reduce cognitive load and lead to better performance was tested in Phase I, whereas Phase II was to investigate that the effectiveness of using graphic calculator strategy may well depend on different levels of mathematics ability. The findings from this study indicated that using graphic calculator can reduce cognitive load and lead to better performance in learning of Straight Lines topic and increase 3-dimensional instructional efficiency index. Thus the graphic calculator strategy is instructionally more efficient than the conventional instructional strategy. In addition, there was no significant interaction effect in the mean overall test performance between the instructional strategy and the level of mathematics ability. Overall, this study has shown that integrating the use of graphic calculators can be beneficial for students and hence provided positive implications for the potential of the tool in teaching mathematics at Malaysian secondary school level.